Taxonomic Affinity of Poaceae Family Based on Morphological Characters - Rahman, Nova Fauziah; Assykuri, Isna Izzmah; Ainilla Khan, Naila Rachmania; Pradana, Bayu Adhel; Akmalia, Hafidha Asni (Biosfer: Jurnal Tadris Biologi, 2022)
This study aims to analyze the relationship among species in the Poaceae family based on their similarities in morphological characteristics. The method used was a taximetry method describing the taxonomic affinity based on morphological characteristics of plants, including leaves, stems, roots, flowers, and fruit. Morphological character data was compiled on Ms Excel, representing the character of each organ and morphological scoring data. Furthermore, the scoring results were analyzed with the NTSys-PC version 2.02i program, and the final results were presented as a dendrogram. The research results show five species of members of the Poaceae family, including Zea mays, Oryza sativa, Saccharum officinarum, Pennisetum purpureum and Cymbopogon citratus, showed that Zea mays and Cymbopogon citratus had the closest affinity with a coefficient of 0.47. In contrast, the most distant affinity was Pennisetum purpureum, with a coefficient of 0.25.ABSTRAK: Tujuan dari penelitian ini untuk menganalisis kekerabatan antar spesies dalam satu famili Poaceae berdasarkan persamaan sifat dan ciri morfologinya. Metode yang digunakan adalah metode taksimetri untuk menjelaskan kekebrabatan fenetik berdasarkan karakter morfologi tumbuhan meliputi daun, batang, akar, bunga, dan buah. Data karakter morfologi disusun pada Matriks Ms. Excel yang mewakili karakter masing-masing organ, dan data skoring morfologis. Selanjutnya hasil skoring dianalisis dengan program NTSys-PC versi 2.02i dan hasil akhir disajikan dalam bentuk dendogram. Berdasarkan hasil penelitian lima spesies anggota famili Poaceae, antara lain Zea mays, Oryza sativa, Saccharum officinarum, Pennisetum purpureum dan Cymbopogon citratus menunjukkan bahwa hubungan kekerabatan fenetik Zea mays dan Cymbopogon citratus memiliki hubungan kekerabatan yang paling dekat dengan koefisien 0.47 sedangkan kekerabatan yang paling jauh adalah Pennisetum purpureum dengan koefisien 0.25.